Commentary on Fiction: A Philosophical Analysis, by Catharine Abell; and Imagining and Knowing: The Shape of Fiction, by Gregory Currie. (4th June 2022) - Gilmore, Jonathan
Abstract: Each of these books offers a richly developed and nuanced account of the nature of fiction. And each poses major challenges to a view about which there is a near-consensus. Catharine Abell draws on a theory of the institutions of fiction to advance a systematic re-envisioning of the metaphysics and epistemology of the contents of stories. Gregory Currie argues that fiction's relationship to the imagination, and the way stories communicate their contents to readers, seriously undermine fiction's cognitive values.